Menerapkan Pemahaman Penyakit Influenza Pada Anak Usia Dini - Anisa Tahira; Rahma Sukmara Putri; Siska Prifiantari (UIN Sultan Maulana Hasanudin Banten, 2022)
Health is the most important thing for every individual, an understanding of health is something that every individual must know, one of which is influenza. This study was designed with a qualitative method, namely the type of research that is descriptive and carried out by means of data analysts in accordance with the facts in the field, this method is a case study that collects data through observation, interviews, and surveys via google form, the aim is to find out the responses from young people in West Java, parents, children and the people of the village of Saguling. The results of this study are that parents, children and young people in the West Java area already understand what, how and how to deal with influenza, the average way they do to avoid influenza is to get enough rest and drink lots of water to increase immunity body.